Validation of the Revised Cardiac Rehabilitation Preference Form in Patients with Post-Percutaneous Coronary Intervention - Fernandez, R.; Salamonson, Y.; Juergens, C.; Griffiths, R.; Davidson, Patricia (Lippincott Williams & Wilkins, 2007)
BACKGROUND: Challenges in achieving optimal participation rates in cardiac rehabilitation (CR) are well described and include factors pertaining to health system and patient and clinical characteristics. Of note, participation rates of patients following percutaneous coronary intervention (PCI) are low. ¦ AIM: The aim of this study was to examine the psychometric properties of the Revised Cardiac Rehabilitation Preference Form (CRPF-R) in an Australian sample following a PCI and to determine the preferences of PCI patients in relation to CR. ¦ METHODS: One hundred forty participants who had PCI completed the self-administered CRPF-R scale. Principal component factor analysis was performed to detect underlying dimensionality of the scale. The internal consistency of the total scale and the subscales was tested with the Cronbach analysis. Comparison for differences in CRPF-R scores, as well as demographic characteristics and CR attendance, was performed. ¦ RESULTS: Factor analysis revealed 2 distinct factors, supporting the validity of a 2-factor structure CRPF-R. Cronbach coefficient values were high, with .87 for the total CRPF-R, .85 for factor 1 (program features), and .81 for factor 2 (convenience features). Women were more likely to place greater importance in the convenience features of a CR program than men. Those who were recommended by a healthcare professional to attend CR were more likely to place greater importance in the program features than those who were not. ¦ CONCLUSIONS: This study has demonstrated the acceptability and utility of the CRPF-R in the Australian setting. In addition, the study also identified important considerations in the structuring and delivery of CR programs.